Strategi Pengembangan Usaha Pengolahan Bebek Palekko (Studi Kasus Palekko Utama di Kelurahan Panreng, Kecamatan Baranti, Kabupaten Sidrap) - Adelia, Dian; Rasidin, Rasidin; Munawarah, Munawarah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This research aims to determine internal and external factors and formulate strategies used in business development and find out what strategies are used in developing palekko duck processing businesses. The data analysis used is qualitative descriptive analysis and SWOT analysis. The results of the research show that the analysis of internal factors and external factors is as follows: strengths: long experience in managing a business, large number of available workers, prioritizing the quality of raw materials and products, distinctive taste of palekko duck, providing good service, well-organized business premises neat and attractive, weakness: processing technology still uses simple equipment, the processing process takes quite a long time (30-40 minutes) in one production, sales promotions do not yet have standard operational procedures (SOP); opportunities: improving economic conditions, increasing interest in palekko ducks, increasingly developing patterns and lifestyles; threats: competition from similar businesses, changes in consumer tastes, fluctuations in the price of palekko ducks, the existence of other types of palekko. A supportive strategy to be implemented in the palekko duck business is the SO strategy, which improves product quality by looking at open market opportunities. and application of communication technology by related agencies, Increasing more innovative products by optimizing the use of quality raw materials to face competitor products,